Personal Branding of Hana Madness as an Mental Disability Doodle Artist - Ekky Ulfah Fauziah; Yanti Setianti; Yustikasari Yustikasari (Universitas Mataram, 2018)
Nowadays, there are still many people who consider that people with mental disabilities are helpless and tends to endanger for the other. Lack of information and education for the community still causes a lot of negative stigma to emerge. Hana Madness, who is a doodle artist with a mental disability background named schizoaffective, then emerged and tried to change the stigma by doing personal branding. The purpose of this study was to find out how the Hana Madness figure then tried to do personal branding activities to change the stigma that still exists. The method used in this study is a type of narrative study with qualitative data. The results of the study show that Hana has a good characteristic in terms of the work she made and also the figure of Hana as an artist. There are not many types of pictures made by Hana in Indonesia, as an artist Hana also focuses more on social impact than money and popularity. Hana has been consistent with the vision and mission that she has, which is to change the stigma that still exists in society towards people with mental disabilities. The conclusion of this study is that personal branding carried out by Hana Madness is based on the abilities she has and with distinctive characteristics from other artists with mental disability backgrounds. Keywords: Personal branding; mental disability; Hana Madness; Doodle art